Afiks-Afiks Derivasional dan Tipe-Tipe Nomina dalam Konstruksi Verba Denominatif Bahasa Indonesia - Nugraha, Danang Satria (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2017)
This research aims to describe the linguistic features of the denominative verb construction (VDn) in bahasa Indonesia (bI). The construction of VDn is a verb derived from nouns, such as mengecat, menyekolahkan, berpakaian, bersepeda. This research utilizes observation in collecting the data and distributional method in analyzing the data. The Data sources are sentences on the use of bI either orally or in writing. This research shows that the VDn constructions, morphologically, are composed of derivational affixes and nouns. The derivational affixes are prefix, circumfix, simulfix, and a combination of affixes. The nouns are root noun, derived form, noun-phrase, animate noun, and inanimate noun.